A point mutant in the promoter of transglutaminase gene dramatically increased yield of microbial transglutaminase from Streptomyces mobaraensis TX1. (January 2022) - Huang, Yimin; Jin, Minfei; Yan, Wenjun; Wu, Qihan; Niu, Yanning; Zou, Chunjing; Jia, Caifeng; Chang, Zhongyi; Huang, Jing; Jiang, Deming; Gao, Hongliang
Graphical abstract: Highlights: Mutant Sm2-1 produced 2.15-fold more TGase than the WT strain. Transcriptional level of TGase gene in the high-yield mutant Sm2-1was 50 times higher than that in the WT strain TX-1. Sequence analysis of the TGase gene found a point mutantion within the -10 region of TGase promoter. Abstract: Microbial transglutaminase (TGase) is widely used in food processing because of its ability to catalyze protein cross-linking. In this study, ultraviolet (UV) mutagenesis was used to create a mutant of Streptomyces mobaraensis TX1 with a high TGase yield, with a maximum yield of 37.51 ± 0.46 U/mL after 32 h of flask fermentation, and a 2.15-fold increase compared to the wild-type (WT) strain. The transcriptional level of the transglutaminase gene increased 50-fold in the mutant strain compared to the WT strain, and a point mutation was found in the promoter of transglutaminase gene. The evaluation results of the promoter function revealed that the high yield of microbial transglutaminase was primarily caused by the point mutation. Our results provided a significant information on the high-yield mechanism of microbial transglutaminase biosynthesis.